Correction: Optical and electrical effects of plasmonic nanoparticles in high-efficiency hybrid solar cells. Issue 38 (23rd September 2020) - Fu, Wei-Fei; Chen, Xiaoqiang; Yang, Xi; Wang, Ling; Shi, Ye; Shi, Minmin; Li, Han-Ying; Jen, Alex K.-Y.; Chen, Jun-Wu; Cao, Yong; Chen, Hong-Zheng
Abstract : Correction for 'Optical and electrical effects of plasmonic nanoparticles in high-efficiency hybrid solar cells' by Wei-Fei Fu et al., Phys. Chem. Chem. Phys., 2013, 15, 17105–17111, DOI: ; 10.1039/C3CP52723A .